Impact of stakeholder perspectives on cost-effectiveness estimates of four specialized nutritious foods for preventing stunting and wasting in children 6-23 months in Burkina Faso. - Shen, Ye.; Cliffer, Ilana R.; Suri, Devika J.; Langlois, Breanne K.; Vosti, Stephen A.; Webb, Patrick.; Rogers, Beatrice L. (Tufts University. Tisch Library., 2020)
Keywords: Cost-effectiveness, Stunting, Wasting, Infant and young children, Supplementary feeding, Opportunity cost, Caregiver, West Africa.; Springer Open.